25-Gauge Vitrectomy with Epiretinal Membrane and Internal Limiting Membrane Peeling in Eyes with Very Good Visual Acuity. (2nd October 2016) - Moisseiev, Elad; Kinori, Michael; Moroz, Iris; Priel, Ethan; Moisseiev, Joseph
ABSTRACT: Purpose : To evaluate the efficacy and safety of pars plana vitrectomy (PPV) in patients with epiretinal membrane (ERM) and preoperative visual acuity (VA) of 20/40 or better. Methods : 44 eyes that underwent PPV and ERM peeling were included in this retrospective study. Data retrieved included demographic information, VA and intraocular pressure (IOP) preoperatively, after 1 month, 6 months and at final visit, presence of metamorphopsia, surgical reports, and occurrence of any complications. Results : Mean preoperative VA was 20/36 (0.24 ± 0.08 logMAR) and had improved to 20/27 (0.13 ± 0.11 logMAR) at the final follow-up (p < 0.001). Thirty (68.1%) eyes had improved by 1 line of vision or more, and 10 (22.7%) achieved final 20/20 vision. Significant improvement in vision was achieved earlier in eyes that underwent vitrectomy combined with cataract extraction. Preoperative OCT scans demonstrated preserved outer retinal layer structure. Conclusions : PPV and ERM peeling is a safe and effective procedure in eyes with very good preoperative VA. PPV combined with cataract extraction offers a faster improvement in VA than PPV alone with deferred cataract surgery. PPV should be considered in symptomatic eyes with ERM and VA of 20/40 or better, in order to preserve and even improve the VA.